Picoeukaryote Plankton Composition off West Spitsbergen at the Entrance to the Arctic Ocean - Kilias, Estelle S; Nöthig, Eva‐Maria; Wolf, Christian; Metfies, Katja (The Journal of eukaryotic microbiology, 2014)
Investigation of marine eukaryotic picoplankton composition is limited by missing morphological features for appropriate identification. Consequently, molecular methods are required. In this study, we used 454‐pyrosequencing to study picoplankton communities at four stations in the West Spitsbergen Current (WSC; Fram Strait). High abundances of Micromonas pusilla were detected in the station situated closest to Spitsbergen, as seen in surveys of picoplankton assemblages in the Beaufort Sea. At the other three stations, other phylotypes, affiliating with Phaeocystis pouchetii and Syndiniales in the phylogenetic tree, were present in high numbers, dominating most of them. The picoplankton community structures at three of the stations, all with similar salinity and temperature, were alike. At the fourth station, the influence of the East Spitsbergen Current, transporting cold water from the Barents Sea around Spitsbergen, causes different abiotic parameters that result in a significantly different picoeukaryote community composition, which is dominated by M. pusilla. This observation is particularly interesting with regard to ongoing environmental changes in the Arctic. Ongoing warming of the WSC could convey a new picoplankton assemblage into the Arctic Ocean, which may come to affect the dominance of M. pusilla.